The performance of West African Dwarf does and their kids at various stocking densities on stylo-based pasture in the subhumid zone of Nigeria - Iji, P.A.; Umunna, N.N.; Alawa, J.P.; Ikwuegbu, O.A. (Cambridge University Press, 1995)
Two studies were conducted between 1991 and 1993 to assess the impact of grazing improved natural pasture at different stocking densities on animal and vegetation responses. In the first grazing season, goats of the West African Dwarf (WAD) breed were grazed at four stocking densities. Wet-season grazing lasted for 14 weeks while assessment was continued until kids were weaned at 120 days of age. There were significant changes in the content of legume and forbs in response to variations in stocking density. Liveweight gain per head was significantly higher at low than at high stocking density. The same trend was maintained with most aspects of reproductive performance. Goats at low stocking density were of a higher body condition score at parturition and had larger litter sizes than does stocked at high stocking density. Kid birth weight and liveweight gain were significantly higher at low than at high stocking density. The overall weight loss in does during nursing was similar at the different stocking densities. In the following year, comparisons were made between three stocking densities on improved and unimproved pastures. Over 14 weeks of wet season grazing, there was a significant decline in available dry matter except at the lowest stocking density on both pasture types. Weight gain per head decreased with increase in stocking density while the reverse was true for weight gain per unit of land. No significant differences were observed for reproductive performance between pasture types or stocking densities. Kid growth rate up to weaning declined with increase in stocking density while kid mortality rose with increase in stocking density. Weight losses in nursing does were higher at low than at high stocking density.